2019
DOI: 10.1007/978-3-030-36030-6_21
|View full text |Cite
|
Sign up to set email alerts
|

Channels of Small Log-Ratio Leakage and Characterization of Two-Party Differentially Private Computation

Abstract: Consider a ppt two-party protocol Π = (A, B) in which the parties get no private inputs and obtain outputs O A , O B ∈ {0, 1}, and let V A and V B denote the parties' individual views.The leakage of Π is the amount of information a party obtains about the event O A = O B ; that is, the leakage ǫ is the maximum, over P ∈ {A, B}, of the distance betweenTypically, this distance is measured in statistical distance, or, in the computational setting, in computational indistinguishability. For this choice, Wullschleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…A recent subsequent work by Haitner, Mazor, Shaltiel and Silbak [19] improved on the above result. They showed that a non-trivial differentially private protocol for computing XOR can be used to construct a standard oblivious transfer protocol (without the infinitely often).…”
Section: Application To Differentially Private Xormentioning
confidence: 74%
See 2 more Smart Citations
“…A recent subsequent work by Haitner, Mazor, Shaltiel and Silbak [19] improved on the above result. They showed that a non-trivial differentially private protocol for computing XOR can be used to construct a standard oblivious transfer protocol (without the infinitely often).…”
Section: Application To Differentially Private Xormentioning
confidence: 74%
“…Achieving external privacy is typically much simpler than the full-fledged notion of Definition 6.1. In particular, functionalities such as XOR (with external privacy) can by implemented using key-agreement protocols, this is in contrast to the full-fledged notion of differential privacy Definition 6.1 that requires oblivious transfer (as was recently shown in [19]).…”
Section: External Differential Privacymentioning
confidence: 99%
See 1 more Smart Citation
“…Our protocol primarily differs in the first step: our aggregator's security guarantee is defined in terms of a metric based on likelihood ratios rather than statistical distance. This alternative metric was also studied in prior work by Haitner, Mazor, Shaltiel, and Silbak [29]. There, the authors construct oblivious transfer from an agreement primitive.…”
Section: Introductionmentioning
confidence: 98%
“…Recent works have made progress on understanding this question for computing Boolean functions, for example, showing that differential private protocol for computing the XOR function with non-trivial accuracy requires the existence of oblivious transfer [23]. Much less progress was made, however, towards understanding the complexity of more natural statistical tasks (e.g., estimating the inner product).…”
Section: Introductionmentioning
confidence: 99%